2020
DOI: 10.3390/biomimetics5030034
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Aspects of Restorative Dentistry Biomaterials

Abstract: Biomimetic has emerged as a multi-disciplinary science in several biomedical subjects in recent decades, including biomaterials and dentistry. In restorative dentistry, biomimetic approaches have been applied for a range of applications, such as restoring tooth defects using bioinspired peptides to achieve remineralization, bioactive and biomimetic biomaterials, and tissue engineering for regeneration. Advancements in the modern adhesive restorative materials, understanding of biomaterial–tissue interaction at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 383 publications
(376 reference statements)
1
103
0
1
Order By: Relevance
“…Ideally, the denture base materials should be highly insert and chemically non-reactive with oral fluids and nutrients. During function, the denture base materials are exposed to a variety of nutrients, which may drastically vary in terms multiple factors, including their chemical nature, pH, and temperature [ 152 ]. Chemically, PMMA materials are organic resins that are negligibly soluble in water, however their solubility is high in organic solvents (such as ketones and esters).…”
Section: Properties Of Pmmamentioning
confidence: 99%
“…Ideally, the denture base materials should be highly insert and chemically non-reactive with oral fluids and nutrients. During function, the denture base materials are exposed to a variety of nutrients, which may drastically vary in terms multiple factors, including their chemical nature, pH, and temperature [ 152 ]. Chemically, PMMA materials are organic resins that are negligibly soluble in water, however their solubility is high in organic solvents (such as ketones and esters).…”
Section: Properties Of Pmmamentioning
confidence: 99%
“… The main components used when constructing biomimetic tissues [ 32 ]. This figure is being reprinted under a Creative Commons BY 4.0 license.…”
Section: Figurementioning
confidence: 99%
“…Both bioink types can be utilized with extrusion printing. Scaffold-based bioinks incorporate cells into an exogenous biomaterial support structure Figure 2 [ 30 , 31 , 32 ]. This supporting scaffold is typically composed of hydrogels, microcarriers (porous, spherical structures to support cell growth and adhesion), or decellularized ECM (dECM) components [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biomimetic materials imitate a biological function and tissue morphology, where such dental materials have been previously investigated and reported [ 16 , 19 , 20 , 21 ]. Biomimetic dental restorative materials for prostheses should imitate the properties of natural tooth and its components, such as enamel and dentin [ 22 ]. Previous reports on the development of restorative materials that mimic tooth morphology and function [ 23 , 24 ] have demonstrated that highly biocompatible materials show promise as next-generation dental CAD/CAM blocks.…”
Section: Introductionmentioning
confidence: 99%